Multiplicación vegetativa de alcornoque mediante embriogénesis somática. - Garcia-Martin, G.; Fernandez-Galiano, E.; Mauri, P. V.; Somática, Embriogénesis (II Congreso Forestal Español, 1997)
In order to obtain cork oak clones from selected individuals, somatic embryogenesis was induced in leaves. Somatic embryos can be continuously subcultured with high proliferation rates. This culture system has sorne limiting factors: low percentage of mature embryos obtained, low rate of shoot emergence during germination and high labour and time consumed. Exogenous addition of ABA (l0-6M) concentration during proliferation increased maturation rateo In the same way addition of. BAP (0,001 mg/l) had a positive effect on shoot production. With the aim to obtain a first approach to automation the best culture media for both culture cycles of maturation in liquid medium were determined.
The following values have no corresponding Zotero field: periodical: II Congreso Forestal Español pub-location: Pamplona
Keywords: ABA; BaP; Cork oak; germination; liquid culture; maturation; somatic embryos

Multiplicación vegetativa de alcornoque mediante embriogénesis somática. (II Congreso Forestal Español, 1997)
In order to obtain cork oak clones from selected individuals, somatic embryogenesis was induced in leaves. Somatic embryos can be continuously subcultured with high proliferation rates. This culture system has sorne limiting factors: low percentage of mature embryos obtained, low rate of shoot emergence during germination and high labour and time consumed. Exogenous addition of ABA (l0-6M) concentration during proliferation increased maturation rateo In the same way addition of. BAP (0,001 mg/l) had a positive effect on shoot production. With the aim to obtain a first approach to automation the best culture media for both culture cycles of maturation in liquid medium were determined.